Flip Chart-based Nutrition Education to Improve Knowledge and Attitude towards Stunting among Adolescent Girls in Sleman Regency - Lina Handayani; Melly Eka Saputri; Heni Trisnowati; Tria Nisa Novianti; Isah Fitriani; Aufatcha Ayutya Suryana; Tania Vergawita; Ardiansyah Jumaedi Nasir; Asa Ismia Bunga Aisyahrani (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Background: Adolescence is a critical stage requiring adequate nutrition for long-term health. Adolescent girls are particularly vulnerable to iron deficiency, which increases the risk of anemia and stunting. Enhancing adolescent girls' knowledge of nutrition through health education, which can be delivered using tools such as flipcharts, can prevent and address stunting. Method: This quasi-experimental study involved 541 adolescent girls aged 12–18 years, with a purposive sample of 91 participants divided into an intervention group and a control group. The intervention group received flip chart-based education, while the control group did not. The study was conducted in Kalurahan Triharjo and Pandowoharjo, Sleman, DI Yogyakarta. Data were collected using validated pre- and post-intervention questionnaires and analyzed with Wilcoxon and paired t-tests. Result: The intervention group showed significant improvements in knowledge and attitudes about nutrition. Knowledge scores increased from 14.42 ± 2.388 at pretest to 19.36 ± 0.883 at posttest (mean difference: 4.94, p = 0.001). Attitude scores rose from 59.04 ± 8.512 to 75.31 ± 2.410 (mean difference: 16.27, p = 0.001). In the control group, smaller increases were observed for both knowledge (mean difference: 0.73, p = 0.001) and attitudes (mean difference: 4.13, p = 0.036). Conclusion: Flip chart-based education effectively improves adolescents’ knowledge and attitudes about nutrition for stunting prevention. However, external exposure to nutrition information in the control group was a limitation. Future research should minimize such exposure by limiting information to basic content for control groups.